Improved tool life in end milling Ti-6A1-4V through workpiece preheating - Ginta, Turnad Lenggo; Amin, A. K. M. Nurul; Lajis, Mohd Amri; Karim, A.N. Mustafizul; Che Daud, Mohd Radzi (EuroJournals Publishing, Inc., 2009)
This paper presents the investigation of tool life improvement in end-milling of Titanium Alloy Ti-6Al-4V through workpiece preheating. End milling tests were conducted on Vertical Machining Centre with full immersion cutting. Induction heating was utilized during end milling for preheating. The titanium alloy Ti-6Al-4V bar was used as the workpiece. Machining was performed with a 20 mm diameter end-mill tool holder fitted with one PCD inserts. All of the experiments were run under room temperature and preheating condition at 315, 450, and 650ºC. Flank wear has been considered as the criterion for tool failure and the wear was measured using a Hisomet II Toolmaker’s microscope. Tests were conducted until an insert was rejected when an average flank wear greater than 0.30 mm was recorded. Cutting force and torque measurements were conducted using the Kistler Rotating Cutting Force Dynamometer. Vibration during cutting was captured using an online vibration monitoring system. Scanning electron microscope (SEM) was also used to investigate the wear morphology. The results led to conclusions that workpiece preheating significantly increases the tool life of PCD inserts in end-milling of Titanium Alloy Ti-6Al-4V.